The Eurhythmics of Swange Dance of the Tiv People of Central Nigeria - Ekpo, Omotolani Ebenezer (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2021)
Eurhythmics in Dalcroze study is defined as the engagement of human body in rhythmic movement and active listening. Jaques-Dalcroze’s involvement of Eurhythmics in music pedagogy is aimed at securing steady position for the body and mind as well as a calculated and unconstrained expression of rhythm. African indigenous music and dance is predominantly functional with intensive assignation of the body and soul of the participants to satisfy the rhythmic drum patterns provided by the musicians. The teaching of music in traditional African settings may be generally informal, yet deliberate. The training technique of the notable indigenous dances in Nigeria informally employ the Dalcroze Eurhythmics teaching technique in the step by step movement pattern and dynamics employed during their group practices, especially with younger members of the group. Among the various traditional dance found in the Tiv clan of central Nigeria, the Swange dance is purposefully selected for this study to validate the relevance of Dalcroze to indigenous Nigerian culture, with regard to music and movement. This paper employ the ethnographic study approach; it combines participatory and observation research methodologies, theoretical engagement, and ample illustrative style of writing, to portray the everyday complexities of music/dance learning among the people.